The Reformation of Waqf Institution to Improve The Potential of Waqf in Indonesia - MUHAMMAD RHEZA RAMADHAN (ITB AAS INDONESIA Surakarta, 2021)
This paper will describe a plan to reform the waqf institution, including the ideal business operations, the structure of the waqf institution, and how to build confidence in the waqf agency in Indonesia. Currently, the growth of waqf has enticed the government to better administer the waqf. Due to a lack of confidence, many individuals are hesitant to pay waqf. As a result, if the government wishes to enhance waqf revenue, the waqf institution in Indonesia should be reformed. Waqf institutions may be bettered in a number of ways. To begin, create new business processes and organizational structures that separate the collection, asset management, and disbursement processes; second, create a single institution supervised by the Ministry of Finance of the Republic of Indonesia to manage endowment funds from waqf; and third, use blockchain to increase the trust of waqf institutions among society.